The crafty art of opera : for those who make it, love it or hate it - Hampe, Michael, 1935-2022 (The Boydell Press, 2016)
Opera has become big business as well as an art form, attracting young and old, true connoisseurs, enthusiasts and celebrities. And while opera singers and superstars sometimes attract a separate following, the stage director's job is often the one that really counts, yet it is a type of specialised knowledge available only to a select few. Here, Michael Hampe brings glimpses of the director's work to a wider audience. 'The crafty art of opera' uncovers the many techniques and rules that should inform an opera's staging: the need for singers to know their orchestra, the importance of space around singers, the gestures of languages, what we all can learn from Mozart, and the primacy of sense over effect, to name but a few. It shows how stories, through music, become tangible and real. Packed with many anecdotes from the author's luminous career, this book is dedicated to opera-lovers who want to understand 'how it is done'; to opera-makers who want to better understand their craft; and, above all, to those who loathe opera, in order to prove them wrong. Eminently readable, it brings both insight and wit from a life spent in opera as director and teacher.